Twin Growth Discordance and Risk of Postpartum Hemorrhage: A Retrospective Cohort Study - Cao, Xiuhong; Luo, Ye; Zhou, Shuangqiong; Zhao, Qingsong; Qin, Xuewei; Liu, Zhiqiang; Xu, Zhendong (Frontiers in Medicine, 2022)
Abstract Background: In recent years, the incidence of postpartum hemorrhage has increased globally. Multiple pregnancies and cesarean sections are well-known risk factors for postpartum hemorrhage. No studies have evaluated the associations between fetal growth anomalies and postpartum hemorrhage in women with twin pregnancies undergoing cesarean section. This study aimed to identify the relationship between fetal growth anomalies and postpartum hemorrhage in women with twin pregnancies undergoing caesarean section. Methods: This retrospective single-center study included 3180 women with twin pregnancies at a tertiary hospital between August 2013 and July 2020. Singleton reference charts were used to assess fetal growth restriction at birth. Discordant growth was defined as an intertwin birth weight difference of ≥20%. Logistic regression analyses were used to evaluate the association between fetal growth anomalies and postpartum hemorrhage. Additionally, sensitivity analysis of abnormal placenta and stratification by twin chorionicity were conducted. Results: The overall incidence of postpartum hemorrhage was 4.3%. Twin growth discordance, especially with fetal growth restriction, was associated with an increased risk of postpartum hemorrhage (adjusted odds ratio [AOR]=1.62, 95% confidence interval [CI], 1.05–2.51, P=0.031; AOR=1.71; 95% CI, 1.08–2.70, P=0.022; AOR=1.98, 95% CI, 1.21–3.25, P=0.006, respectively). After stratification, this relationship persisted in dichorionic twins (OR=1.71, 95% CI, 1.04–2.82, P=0.036; OR=1.90, 95% CI, 1.13–3.21, P=0.016; OR=2.48, 95% CI, 1.41–4.38, P=0.002, respectively). However, no significant association was observed in monochorionic twin pregnancies. Conclusion: Growth discordance, especially complicated by fetal growth restriction, was associated with an increased risk of postpartum hemorrhage in women with twin pregnancies undergoing caesarean section, and was more evident in patients with dichorionic twins.